Кадрове забезпечення місцевих органів політичної поліції Російської імперії (друга половина ХІХ – початок ХХ ст.) - Литвин, Катерина; Litvin, Catherine (Східноєвропейський національний університет імені Лесі Українки, 2017)
Research is devoted to the analysis of the methods of selection and training of personnel for provincial gendarmerie offices and security departments of the second half of the XIX – beginning of the XX century. An attempt was made to identify the main features that should have been inherent in candidates for the service in the political police and how real gendarmes they owned. The article shows the evolution of the gendarme training system, its separate stages as well as the factors that influenced the change in the system of their professional training. The role of training courses for gendarmes and their role in the future career growth of an officer is disclosed. Проаналізовано методи відбору та підготовки кадрів для губернських жандармських управлінь та охоронних відділень другої половини ХІХ – початку ХХ ст. Зроблено спробу виокремити основні риси, які повинні бути притаманні кандидатам на службу в політичній поліції, та фактори, що впливали на зміну системи їх професійного навчання.
Staffing of Local Bodies of the Political Police of the Russian Empire (Second Half of the XIX - Early XX Centuries)
Keywords: політична поліція; кадрове забезпечення; губернське жандармське управління; охоронне відділення; Російська імперія; political police; personnel support; provincial gendarmerie administration; security department; Russian empire